Prevention and Handling of Covid-19 in the Work Area of UPTD Puskesmas Tanah Baru through Collaborative Governance - Rusliandy Rusliandy; Mira Miranti Puspitasar (Budapest International Research and Critics University, 2021)
The Covid-19 pandemic has become a multidimensional problem, no longer a health problem. The increase in residents exposed to COVID-19 in the working area of the Tanah Baru Health Center UPTD continues to increase and efforts to prevent and handle COVID-19 cannot only be handled by the Puskesmas, but require collaboration between stakeholders from elements of the community, business actors and the government. The method used is a qualitative approach with an analytical knife is Collaborative Governance. Sources of data obtained through primary data and secondary data, while data collection techniques were carried out through in-depth interviews, literature review, and observation. The results showed that the collaborative governance approach was effective in preventing and handling COVID-19 as long as the resources owned by the stakeholders involved were still able to contribute and provide services in handling COVID-19. However, the implementation of collaborative governance began to face various obstacles when there was a radical surge in residents exposed to COVID-19 which resulted in health facilities being unable to carry out treatment, referral hospitals were full, many health workers were exposed to COVID-19, and the ambulance fleet was limited. This condition resulted in various complaints from the public. To overcome these problems, it is necessary to optimize the participation of 3 elements, namely the government, society and the business world. Forms of optimizing these roles include increasing capacity, resources and health infrastructure, complying with 5M, reducing mobilization, and carrying out vaccinations.